A Study on Postnatal Depression among Women Attending Tertiary Care Hospital in Davanagere, Karnataka - Sandhya Rani Javalkar; Vanitha S S (National Journal of Community Medicine, 2018)
Introduction: Postnatal depression (PND) is a public health problem as it arises as a common complication of childbearing and it significantly affects women and their families